Analysis of the Overall Equipment Effectiveness Losses and the Application of Continuous Improvement Techniques to Increase Productivity in Ecolab Leeds - Gonzalez Puente, Marisela (2014)
At present customers’ expectations have increased worldwide for practically all businesses. Quality and cost have become a requisite, with customers now expecting companies to offer more flexibility in terms of product mix, or improved speed of deliveries. Ecolab is a company that specialises in producing a range of liquid and cream sanitising products. They have addressed this situation by formulating plans to improve productivity of its two main production lines with an initial target of 3-5% improvement by the end of 2014. For the long-term the company is targeting to achieve results of 75% Overall Equipment Effectiveness (OEE) in both of their main production lines Excel and Purdy. As a starting point in achieving this, the present dissertation reviews and investigates the current measurement system of Ecolab to determine its level of accuracy and the possibility of improving such system in order to have more accurate measures. Additionally, it aims identify unaccounted OEE losses in order to suggest improvements based on the Lean literature. The methodology used consisted of observation of the current state, an analysis of the information collected, and recommendations to help improve upon such issues. The results of the conceptual and empirical research pointed out alternative expressions to calculate OEE with potentially more benefits for the company in terms of visibility of the performance. The major issues affecting accuracy of OEE were related to the theoretical cycle time, and issues originated due to manual data collection. Suggestions such as standard-work and training are made to improve, it is also considered the implementation of software packages to automate data collection whose benefits can be highly favourable to the company in the long-term. In the research of unaccounted OEE losses it was found that minor stops are often not considered by operators. However, as they occur frequently their effects on productivity could be high at a long-term; as part of the suggestions to improve this, Lean techniques such as visual factory elements, 5S, and super-market are considered. Finally, an approach to multi skill direct workforce is described as a way to reduce planned time by covering breaks and meetings. Lean is by no means a shortcut to achieve high performance within companies, its success depends having good foundations to then be able to select the methods and tools that better fit for the company needs. Trained people is one of the most common characteristics that most if not all the lean techniques embrace as part of their foundations. Accuracy of performance metric is critical in order to take decisions in the right direction.